The relationship between sense of community belonging and self-rated mental health among Canadians with mental or substance use disorders. (3rd March 2020) - Palis, Heather; Marchand, Kirsten; Oviedo-Joekes, Eugenia
Abstract: Background : One-third of Canadians meet the criteria for a mental or substance use disorder at some point in their lifetime. While prevention and treatment efforts have been focused on the individual, studies suggest the importance of incorporating social and community factors. Aims : This study investigates the relationship between community belonging and self-rated mental health among Canadians with mental or substance use disorders. Methods : The Canadian Community Health Survey-Mental Health (2012) is a nationally representative survey of Canadians aged 15 years and older ( n = 25, 113). The present analytic sample is comprised of respondents reporting a mental or substance use disorder in the previous 12 months ( n = 2628). The relationship between community belonging and self-rated mental health is depicted with a multivariable multinomial logistic regression model. Results : Self-rated mental health was reported as follows: poor or fair (38.1%); good (33.7%); and very good or excellent (28.2%). In the multivariable multinomial model, a positive relationship was observed. Those reporting very strong compared to very weak community belonging had an increased odds of better mental health. Conclusions : Findings indicate the importance of social and community-based interventions to effectively engage and retain individuals in services for the prevention and treatment of mental and substance use disorders.